Investigation of the soil deformation around laterally loaded deep foundations with large diameters - Li, Xiaojuan; Dai, Guoliang; Zhu, Mingxing; Zhu, Wenbo; Zhang, Fan (Acta geotechnica, 2024)
In projects such as highway bridges and offshore wind farms, understanding the kinematics of soil layers and their displacement is important for accurately predicting the behavior of caissons and monopiles under lateral loads. To better predict the distribution of soil deformation around the foundations, this paper presents an extensive usage of the energy-based variational method in laterally loaded deep foundations (caissons or monopiles) with very large diameters. By adding an assumption of soil deformation in multilayered soils, the displacement distribution around the foundations can be better described. The responses of deep foundations were obtained by minimizing the potential energy and virtual work of the foundation-soil system. After that, static lateral loading tests on two caissons with the same embedment depth of 36 m and the same diameter of 6 m were performed, and the displacement field in soils and the deflection profiles of the caissons were measured. Results show that the lateral displacement and the decay distribution fields calculated from the theory in this paper agree with the measured data from the static loading tests and the corresponding finite differential method (FDM) results. At last, a series of case studies performed by MATLAB and FDM analyses were also conducted to study the influence of u z on the response of foundations, as well as the influence of foundation parameters and soil modulus on the value of ϕ z .